Using Drama Therapy to Enhance Maternal Insightfulness and Reduce Children’s Behavior Problems - Feniger-Schaal, Rinat; Koren-Karie, Nina (Frontiers in Psychology, 2021)
Maternal insightfulness, or the capacity to see things from the child's point of view, is considered to be a crucial construct for therapeutic change (Oppenheim & Koren-Karie, 2009). In the present study, we aimed to implement the knowledge gleaned from attachment research on maternal insightfulness into clinical practice, to create an intervention program for mothers of children at risk due to inadequate parental care. We used drama therapy to “practice” maternal insightfulness in more “experiential” ways, because the use of creative expressive means may be accessible and effective for the target population of the study and help improve maternal care. We used a manualized ten-week drama therapy group intervention focusing on the core concepts of maternal insightfulness: insightfulness, separateness, complexity, and acceptance. We used various dramatic means to explore and experience these components of maternal insightfulness (masked for review). Forty mothers of children at risk took part in eight groups of parental insightfulness drama therapy (PIDT). To evaluate the efficacy of the intervention, we used the Insightfulness Assessment (IA) interview (Koren-Karie et al., 2002), which produces ten scales and a final classification of positive insightfulness and non-insightfulness. The Child Behavior Check List (CBCL) (Achenbach, 1991) was used to evaluate change in children’s behavior problems. The assessment took place at three time points: before the intervention (T1), right after the end of the intervention (T2), and six months following the intervention (T3). Results at T2 showed a significant improvement compared to T1 in some of the maternal insightfulness scales, but not in the maternal insightfulness categorical classification. At T3, there was a significant change in the classification of the mothers, from non-insightful to positively insightful. At T3, there was also a significant decline in the children’s externalized and general behavioral problems. The results of this study contribute to evidence-based practice of using drama therapy in the treatment of mothers and children at risk.